Multilingual processing of speech via web services. (September 2017) - Kisler, Thomas; Reichel, Uwe; Schiel, Florian
Highlights: New software paradigm for linguistic/phonetic tools: webservices. Webservices as building blocks for complex systems. BAS CLARIN webservices: a free service to the scientific community. Multilingual automatic segmentation and labelling of speech into words and phones. Multilingual automatic text-to-phoneme conversion webservice. Abstract: A new software paradigm `Software as a Service' based on web services is proposed for multilingual linguistic tools and exemplified with the BAS CLARIN web services. Instead of traditional tool development and distribution the tool functionality is implemented on a highly available server that users or applications access via HTTP requests. As examples we describe in detail five multilingual web services for speech science operational since 2012 and discuss the benefits and drawbacks of the new paradigm as well as our experiences with user acceptance and implementation problems. The services include automatic segmentation of speech, grapheme-to-phoneme conversion, syllabification, speech synthesis, and optimal symbol sequence alignment.